Additive impact of alfacalcidol on bone mineral density and bone strength in alendronate treated postmenopausal women with reduced bone mass - Felsenberg, D; Bock, O; Börst, H; Armbrecht, G; Beller, G; Degner, C; Stephan-Oelkers, M; Schacht, E; Mazor, Z; Hashimoto, J; Roth, H-J; Martus, P; et al. (Journal of musculoskeletal & neuronal interactions, 2011)
Assessment of additive impact of alfacalcidol 1 μg daily (Alfa) on bone mineral density (BMD) and on bone strength in postmenopausal women treated with alendronate 70 mg weekly + 500 mg calcium daily. In a randomized, double-blind, placebo controlled study, 279 postmenopausal women with osteoporosis or osteopenia participated (intention to treat analysis [ITT]; aged 73.6∓4.7 years) and were treated with 70 mg alendronate (ALN) weekly and 500 mg calcium daily for 36 months. In addition, these patients received either 1 μg alfacalcidol (Alfa) or placebo (PLC) daily. BMD was measured with Dual-Energy-X-ray-Absorptiometry (DXA) at the lumbar spine and proximal femur and at forearm and tibia with peripheral quantitative computed tomography (pQCT) at regular intervals for 36 months. DXA-BMD of lumbar spine (L1-4) increased after 36 months, by 6.65% (p<0.0001) in the Alfa/ALN group versus 4.17% (p<0.0001) in the PLC/ALN group. Group difference was significant after 3 years (p=0.026). At the end of the study, significant differences were found in favor of the Alfa/ALN group in trabecular density (tibia) (p=0.002), cortical density (midshaft tibia) (p=0.043), and bone strength (p=0.001). The remaining parameters showed no differences between the treatment arms, apart cortical bone density at midshaft radius. Alfacalcidol significantly increases the efficacy of alendronate treatment in osteopenic/osteoporotic postmenopausal women on spinal DXA-BMD, cortical and trabecular BMD of the tibia and also bending stiffness of the tibia.